2022
DOI: 10.3390/ijerph19063663
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Volatile Compound Transference through Firefighter Turnout Gear

Abstract: There is high concern about the exposure of firefighters to toxic products or carcinogens resulting from combustion during fire interventions. Firefighter turnout gear is designed to protect against immediate fire hazards but not against chemical agents. Additionally, the decontamination of firefighter personal protective equipment remains unresolved. This study evaluated the feasibility of a screening method based on headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) in combination with chemom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Yang et al [64], instead, analyzed urinary samples to evaluate candidate metabolites for the diagnosis of inherit metabolomic diseases. Aliaño-González et al [65] applied PCA and LDA to GC data of firefighters' coats to discriminate those exposed to fire from the non-exposed ones, in order to identify toxic substances to which firefighters can be exposed. Two interesting works of Bogdal et al [66,67] focused on tracing gasoline residues in fire debris, with the aim of identifying arsons.…”
Section: Gas Chromatography (Gc) and Chemometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al [64], instead, analyzed urinary samples to evaluate candidate metabolites for the diagnosis of inherit metabolomic diseases. Aliaño-González et al [65] applied PCA and LDA to GC data of firefighters' coats to discriminate those exposed to fire from the non-exposed ones, in order to identify toxic substances to which firefighters can be exposed. Two interesting works of Bogdal et al [66,67] focused on tracing gasoline residues in fire debris, with the aim of identifying arsons.…”
Section: Gas Chromatography (Gc) and Chemometricsmentioning
confidence: 99%
“…In the last few decades, Ion Mobility Mass Spectroscopy (IMS) is gaining great attention as detector for GC analysis [65,81], as an alternative to traditional MS or as a pre-filter before it. Indeed, IMS performs a further separation of analyte after GC column by ionizing the molecules and subjecting them to an electric field, carrying them toward a Faraday plate (or the MS chamber) while a drift gas flows in the opposite direction.…”
Section: Gas Chromatography (Gc) and Chemometricsmentioning
confidence: 99%
“…3,51 The available data on the exposure of firefighters to toxic flame retardants on bunker gear are based on the contamination of the gear during fire operations. 7,52,53,59,60…”
Section: Firefighter Exposure To Flame Retardantsmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) has concluded that the firefighter occupational exposures should be classified carcinogenic to humans given the limited research and evidence. 7,52,56 However, literature related to firefighters’ exposure to the toxic PAH released during fires remains limited. 6 A suspected critical route that calls for further scrutiny is the volatilization of toxic flame retardants in the bunker gear of firefighters.…”
Section: Firefighter Exposure To Flame Retardantsmentioning
confidence: 99%
See 1 more Smart Citation